Whole genome comparisons of serotype 4b and 1/2a strains of the food-borne pathogen Listeria monocytogenes reveal new insights into the core genome components of this species - Nelson, Karen E. (Oxford University Press, 2004)
The genomes of three strains of Listeria monocytogenes that have been associated with food-borne illness in the USA were subjected to whole genome comparative analysis. A total of 51, 97 and 69 strain-specific genes were identified in L.monocytogenes strains F2365 (serotype 4b, cheese isolate), F6854 (serotype 1/2a, frankfurter isolate) and H7858 (serotype 4b, meat isolate), respectively. Eighty-three genes were restricted to serotype 1/2a and 51 to serotype 4b strains. These strain- and serotype-specific genes probably contribute to observed differences in pathogenicity, and the ability of the organisms to survive and grow in their respective environmental niches. The serotype 1/2a-specific genes include an operon that encodes the rhamnose biosynthetic pathway that is associated with teichoic acid biosynthesis, as well as operons for five glycosyl transferases and an adenine-specific DNA methyltransferase. A total of 8603 and 105 050 high quality single nucleotide polymorphisms (SNPs) were found on the draft genome sequences of strain H7858 and strain F6854, respectively, when compared with strain F2365. Whole genome comparative analyses revealed that the L.monocytogenes genomes are essentially syntenic, with the majority of genomic differences consisting of phage insertions, transposable elements and SNPs.